Benzodiazepine Use as an Independent Risk Factor for HIV Infection in a Canadian Setting - Ickowicz, Sarah (Drug Alcohol Depend, 2015)
BACKGROUND: Although the harms of prescription drug diversion are of growing international concern, the potential impact of prescription drug use on HIV infection has not been well assessed. We evaluated whether benzodiazepine use was associated with HIV seroconversion among a cohort of persons who inject drugs (PWID) in a Canadian setting. METHODS: Between May, 1996 and November, 2013, data were derived through a prospective cohort study of PWID in Vancouver, Canada. A total of 1,682 baseline HIV negative participants were followed for a median of 79.5 months (interquartile range: 32.1 – 119.1), among whom 501 (29.8%) reported benzodiazepine use at baseline, and 176 seroconverted during follow-up, equal to an incidence density of 1.5 (95% Confidence Interval [CI]: 1.3 – 1.7) cases per 100 person-years. Poisson regression with time-dependent variables was used to assess whether benzodiazepine use was associated with the time to HIV seroconversion. RESULTS: After adjustment for potential confounders, benzodiazepine use (Adjusted Rate Ratio: 1.50; 95% CI: 1.01 – 2.24) was independently associated with a higher rate of HIV seroconversion. CONCLUSIONS: Benzodiazepine use was an independent risk factor for HIV seroconversion among PWID in this setting. Greater recognition of the safety concerns related to benzodiazepine medications including d iversion are needed.